Role of Laser Peripheral Iridoplasty in Acute Attack of Primary Angle Closure Glaucoma - Israr A. Bhutto, P.S Mahar, Dilshad Laghari (Pakistan Journal of Ophthalmology, 2010)
Purpose: To study the effect of laser peripheral iridoplasty (LPIp) on the intra ocular pressure (IOP) and the anterior chamber angle in the patients with an acute attack of primary angle closure glaucoma (PACG), non-responsive to the medical therapy. Materials and Methods: The study was carried out at Isra Postgraduate Institute of Ophthalmology, Karachi, from April, 2005 to June, 2009. Sixteen patients with the mean age of 61.36 year SD + 3.38 year, (10 female & 6 males) were treated with LPIp, when their IOP remained elevated with closed angle despite maximum medical treatment, comprising of intravenous Mannitol 20%, topical beta blocker and Pilocarpine. Results: The pre-laser IOP of the patients ranged between 36 mmHg to 48 mmHg with mean IOP of 41.64mmHg SD + 4.03mmHg. The post laser IOP measured at 1 hour ranged between 9 mmHg to 22 mmHg with the mean IOP of 14.36 SD + 4.70 mmHg. Pre-laser gonioscopy revealed total appositional closure of the angle in all 4 quadrants. After laser, 11 patients had grade II angle (Shaffer’s classification), revealing posterior part of the trabecular meshwork in 2 quadrants, while 5 patients had grade II angle in all the quadrants. Conclusion: LPIp is a safe and effective procedure in controlling the IOP in patients, with an acute attack of PACG, unresponsive to the medical therapy with opening of the anterior chamber angle